2022
DOI: 10.1364/oe.447972
|View full text |Cite
|
Sign up to set email alerts
|

Flexible chalcogenide glass large-core multimode fibers for hundred-watt-level mid-infrared 2-5 µm laser transmission

Abstract: The rapidly-developed high-power mid-infrared 2-5 µm laser technology requires a compact, flexible low-loss glass fiber for power delivery or laser generation. With the broadest bandwidth of low-loss transmission window in mid-infrared region amongst all mid-infrared glass fibers, chalcogenide glass fiber is the best candidate covering the whole 2-5 µm range. Multi-hundred-watt high-power delivery for 5.4-µm CO laser was previously demonstrated in a multimode chalcogenide fiber with a 1-mm-diameter large core,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The As–S glass material was chosen for fabricating the 3 × 1 fiber combiner in this study due to its excellent MIR transparency, good resistance to crystallization, and relatively high laser damage threshold 13,14 . The structure of the fiber combiner is shown in Figure 1A.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The As–S glass material was chosen for fabricating the 3 × 1 fiber combiner in this study due to its excellent MIR transparency, good resistance to crystallization, and relatively high laser damage threshold 13,14 . The structure of the fiber combiner is shown in Figure 1A.…”
Section: Methodsmentioning
confidence: 99%
“…The As-S glass material was chosen for fabricating the 3 × 1 fiber combiner in this study due to its excellent MIR transparency, good resistance to crystallization, and relatively high laser damage threshold. 13,14 The structure of the fiber combiner is shown in Figure 1A. The preparation process of the combiner includes the preparation of highpurity glass, fiber fabrication, capillary tube preparation, fiber bundle tapering, fiber taper region cutting, output fiber fusion splicing, and fiber combiner armoring.…”
Section: Preparation Of Mid-infrared Fiber Combinermentioning
confidence: 99%
See 1 more Smart Citation
“…For pulse durations of 190 ns, the maximum input energy of the pulsed laser was 2.3 mJ, corresponding to a power density of 28.2 MW/cm 2 . In 2022, Qi et al [24] demonstrated a power transmission of 100 W in multi-mode As-S fibers using a high-power 2 µm erbium-doped silicon fiber laser source. With effective cooling, the 200 µm core diameter As-S multimode fibers resisted an incident laser power of 120 W, transmitted 63 W, and handled an incident power density of up to 472 kW/cm 2 .…”
Section: Progress In Laser Delivery Below 5 µM Wavelengthmentioning
confidence: 99%
“…However, fabrication difficulties have significantly hindered the production of long lengths of fiber and hence applications requiring long-distance MIR laser delivery. Current delivery distances have been limited to a few meters' length [10][11][12][13][14]. Moreover, the low damage thresholds, small mode areas, and high nonlinearity of these fibers are also a hindrance to their use in high-power single-mode MIR beam delivery.…”
mentioning
confidence: 99%